PENYULUHAN TB PARU DI KELURAHAN SIMALINGKARPULMONARY TB COUNSELING IN SIMALINGKAR VILLAGE - Pane, Halimah Fitriani; Ginting, Mardan; Siregar, Siti Main; angin, Susanti Perangin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Tuberculosis (TB) is one of the top 10 causes of death and the leading cause of a single infectious agent. In 2019, an estimated 10 million people were infected with TB worldwide. 5.6 million men, 3.2 million women and 1.2 million children. The percentage of pulmonary TB of all types in male people is greater than in female people because men pay less attention to maintaining their own health and men often come into contact with risk factors compared to women. Several risk factors that cause the occurrence of tuberculosis are sociodemographic factors, environmental factors, and comorbid factors. Based on a survey conducted by TIM, it is known that the number of people suffering from pulmonary TB in the Simalingkar National Housing Complex, Medan Tuntungan District is currently increasing. Trigger factors are smoking habits, contact history, or the presence of comorbid factors. The aim of this community service activity is to provide education about the prevention and control of Tuberculosis infection in the community. The methods used are counseling and conducting sputum examinations. The results of the sputum examination carried out in the laboratory showed that of the 110 people examined, 1 person (0.9%) was positive for BTA. Meanwhile, 109 people had negative BTA results (99.1%).